Dronabinol has preferential antileukemic activity in acute lymphoblastic and myeloid leukemia with lymphoid differentiation patterns. Issue 1 (December 2016) - Kampa-Schittenhelm, Kerstin; Salitzky, Olaf; Akmut, Figen; Illing, Barbara; Kanz, Lothar; Salih, Helmut; Schittenhelm, Marcus
Abstract Background It has been previously demonstrated in several cancer models, that Dronabinol (THC) may have anti-tumor activity – however, controversial data exists for acute leukemia. We have anecdotal evidence that THC may have contributed to disease control in a patient with acute undifferentiated leukemia. Methods To test this hypothesis, we evaluated the antileukemic efficacy of THC in several leukemia cell lines and native leukemia blasts cultured ex vivo. Expression analysis for the CB1/2 receptors was performed by Western immunoblotting and flow cytometry. CB-receptor antagonists as well as a CRISPR double nickase knockdown approach were used to evaluate for receptor specificity of the observed proapoptotic effects. Results Meaningful antiproliferative as well as proapoptotic effects were demonstrated in a subset of cases – with a preference of leukemia cells from the lymphatic lineage or acute myeloid leukemia cells expressing lymphatic markers. Induction of apoptosis was mediated via CB1 as well as CB2, and expression of CB receptors was a prerequisite for therapy response in our models. Importantly, we demonstrate that antileukemic concentrations are achievable in vivo. Conclusion Our study provides rigorous data to support clinical evaluation of THC as a low-toxic therapy option in a well defined subset of acute leukemia patients.